PENGARUH PEMBIAYAAN DAN TINGKAT BAGI HASIL TERHADAP TINGKAT KESEJAHTERAAN DI INDONESIA DILIHAT DARI PERTUMBUHAN PDB - Atika, Atika (Universitas Muhammadiyah Surakarta, 2018)
The purpose of this study is to assess empirically the effect of financing channeled by the Sharia Bank and the profit-sharing rate to GDP growth. With this research is also expected to explain that sharia banks are still new when compared with conventional banking also have an influence on the economy in Indonesia.The material used in this study is the financing variables are funding provided by a party to other parties to support the planned investment both alone and institutions. Financing variables in this research is all financing channeled by syariah bank. The profit-sharing variable is the form of return (the acquisition of business activity) of the investment contract from time to time, uncertain and not fixed on a Sharia bank. The size of the acquisition depends on the results of the business actually obtained by the Sharia bank. As well as the variable GDP (Gross Domestic Product) is the market value of all final goods and services produced within a country within a certain period of time. Data obseration used is data of those variables in the last 11 years that is year 2001 s / d 2011. Data obtained from BPS Indonesia and Bank Indonesia.The data analysis used is classical assumption test which includes: Normality Test, Autocorrelation Test, Heterokedasity Test, Multicolinearity Test besides also using Multiple Linear Regression Test and Partial Test, Simultaneous Significance Test (F statistic Test) and Coefficient of Determination (adjusted ). To test above the researcher using SPSS software program version 16.The result of research got R-Square value 0,666 or 66,6% means that 66.6% of GDP variable can be influenced by financing variable and profit sharing and 33,4% is explained by other variable which not examined. From the calculation proves that the financing channeled by sharia banks has no significant effect to the welfare of the community (seen from GDP growth) while the profit sharing rate has a significant influence on the welfare of the community.Â Keywords: financing, profit sharing, welfare